Photocatalytic Properties of All Four Polymorphs of Nanostructured Iron Oxyhydroxides. Issue 11 (26th October 2016) - Jelle, Abdinoor A.; Hmadeh, Mohamad; O'Brien, Paul G.; Perovic, Doug D.; Ozin, Geoffrey A.
Abstract: Four different polymorphs of nanostructured iron oxyhydroxides, namely; goethite (α‐FeOOH), akaganeite (β‐FeOOH), lepidocrocite (γ‐FeOOH), and feroxyhyte (δ‐FeOOH) were synthesized and fully characterized by X‐ray diffraction, electron microscopy, UV/Visible spectrophotometry, Brunauer–Emmett–Teller (BET) measurements, and X‐ray photoemission spectroscopy. The relationship between these iron oxyhydroxide polymorphs and their photocatalytic properties was explored by examining the extent of methylene blue (MB) degradation by each polymorph under visible‐light irradiation. Feroxyhyte exhibited the best photocatalytic properties and degraded 85 % of the MB dye in five hours. In comparison, goethite, akaganeite, and lepidocrocite degraded only 40 %, 35 %, and 30 % of the MB in five hours, respectively. To understand this trend, the surface area, particle size and shape, and electronic band properties were systematically studied and discussed. It was found that the rate of MB degradation relates mainly to the surface area of the FeOOH polymorphs more than any other factor. This is the first report of a comparative study of the physical, electronic, and photocatalytic properties of all four polymorphs of nanostructured iron oxyhydroxides. Abstract : Pick a polymorph : The relationship between the four different polymorphs of nanostructured iron oxyhydroxides and their photocatalytic properties was explored by examining the extent of methylene blue (MB) degradation under visible‐light irradiation. Feroxyhyte exhibited the best photocatalytic properties, while goethite, akaganeite, and lepidocrocite were less effective. To understand this trend, the surface area, particle size and shape, and electronic band properties were systematically studied and discussed.